“Our brokenness kind of connects us”: exploring social justice topics through read-alouds in a ninth-grade classroom - Hoppe, Kayln Jealee (Kansas State University, 2022)
For decades, K-12 teachers across the United States have read aloud to their students, whether it be to model fluent reading, to promote vocabulary acquisition, or out of pure enjoyment. As social justice becomes a more prevalent topic in classrooms across the country, interactive read-alouds are being used to introduce and discuss complex and delicate topics, like human rights and social justice. While students at all junctures of development and learning embrace and benefit from reading aloud, existing research primarily takes place in elementary school settings. Furthermore, literature used to explore social justice issues usually involves picture books rather than longer texts like chapter books. This study was designed to gain insight into how a classroom teacher facilitated a nonfiction chapter book read-aloud and how the students responded to the social justice themes represented in the chapter book. The study took place over the span of 18 days in a Midwest ninth-grade classroom. The theoretical underpinnings that framed the study were constructivism, transactional theory of reader response and critical literacy. Data was collected and analyzed using qualitative case study principles. Study results reveal four emerging themes across the research questions, including expressive reading; spontaneity; redemption; empathy; and awareness.
Keywords: Read-aloud; Social justice; Young adult literature; Secondary education; Literacy